ANALYSIS OF EFFICIENCY OF TEAM BASED LEARNING (TBL) TECHNOLOGY - Baildinova, Klara; Zhunusova, Aigul; Kuanysheva, Anar; Maukayeva, Saule; Kozhanova, Saule; Zhanaspayev, Marat; Nuralinova, Gulnar; Tusupova, Karlygash; Achmetova, Almira; Orazalina, Ainash (European Scientific Journal, ESJ, 2014)
Team based learning is one of the effective technologies used in teaching in preclinical and clinical disciplines in Semey State Medical University. TBL consists of the following stages: individual testing, group testing, clinical case, practical skills, individual testing. During team based learning vertical and horizontal integration is used. Integration is implanted between theoretical disciplines, theoretical and clinical disciplines and between clinical subjects. 100 students and 50 teachers were surveyed about efficiency of TBL. Teachers and students marked that team based learning technology helps to develop competencies, associated with knowledge, practical skills and attitude: Team based learning improves â€œknowledge and understanding in study areaâ€; â€œpractical skillsâ€, â€œclinical thinkingâ€; â€œcommunication skillsâ€, â€œskills of scientific researchâ€, â€œteam work skillsâ€. Students put the overage mark of TBL technology â€“ 3,33, teachers â€“ 3,67. Feed back of students and teachers allows to correct content of TBL. Team based learning increases motivation of students, individual and group responsibility, improves communication skills, clinical thinking, reveals leadership. .